Effect of Cellulytic Enzyme Supplementation (Extracted from Chatomium thermophyle) on Production Performance and Economic Appraisal in Aged Layers Using High Fiber Diets - Atia Bahseer,; A. Haq,; I. Zahoor, (Journal of Basic & Applied Sciences, 2014)
One hundred and twenty white leghorn layers of 80 weeks having uniform body weight were randomly divided into 15 experimental units of 8 birds each and reared under standard managemental conditions. Five treatments (each having three replicates) i.e. control T1 (commercial layer mash), T2 (layer mash having 6% fiber + 1X enzyme), T3 (layer mash having 8% fiber + 1X enzyme), T4 (layer mash having 6% fiber + 2X enzyme) and T5 (layer mash having 8% fiber + 2X enzyme) were randomly allotted to experimental units. Egg production, egg weight and feed consumption were recorded for eight weeks. Egg mass, feed conversion ratio/dozen egg and feed conversion ration/kg egg mass was also calculated. Data was analyzed statistically using analysis of variance technique under completely randomized design. Treatment means were compared using least significant test. It was found that egg production increased significantly by the T2 but was non-significant with the control group. The different treatments showed significant decrease in feed consumption as compared with control group. Significant improvement in egg mass was found in control group and was non-significant with T2 and T4. There was significant effect of enzyme supplementation on feed conversion ration/dozen egg and feed conversion ratio/kg egg mass. T2 and T4 showed best feed conversion ratios per dozen and per kg egg mass. Maximum profit/bird was observed in T2 followed by T4, T5, T3 and T1, respectively